CRUEL JOKES AND NORMATIVE COMPETENCE. Issue 1 (4th December 2018) - Shoemaker, David
Abstract: Some moral responsibility theorists think that certain agents (like psychopaths) can be morally responsible—and morally criticizable—for their actions and attitudes even though they lack any competence in grasping or responding to moral norms (a blindness to moral reasons that is typically called "normative incompetence" or, more accurately, "moral incompetence"). In this essay, I provide a new argument against these theorists by exploring the intersection between two normative domains, the funny and the moral. There are, it turns out, interesting and significant ways that properties from each domain bear on reasons to respond in the other, and so there are interesting and significant ways in which people's responses to cruel jokes or insult humor may be criticizable. I then survey various personality and psychological impairments that seem to undercut criticizability in this intersecting domain. Learning about these people and their impairments yields a wealth of information about what true normative competence actually requires, as well as why competence of the specifically moral variety really is required for moral criticizability .